The influence of Transit Area in Public Open Space of Losari Beach Makassar Pavilion on the Activities of Group Visitors - Miftahul Jannah b; Triyatni Martosenjoyo; Rosady Mulyadi (EPI International Journal of Engineering, 2021)
Urban communities are social beings who have a high level of activity. One of the activities to release fatigue is a refreshing type of activity. A developing city like Makassar needs open space for the public as a container for community activities, including refreshing activities. The Losari Beach Pavilion is present as an open public space that is visited by the majority of visitors in groups to carry out refreshing activities. This public space has a space configuration whose design is available in several parts of the room as a stopover for visiting activities. This part of the space shows that the activities are overlapping so that space is used in the transit space and some of it becomes empty space. Therefore, this research was conducted to explain the effects of what happens to transit space and empty space, in this case the space that is not functionally stopped. This study used the descriptive qualitative method. The data collection technique uses the behavior mapping method by recording activities and sketches to get an image of the activity pattern carried out by group visitors then presented in tables, pictures and descriptions. The results of the study show that the transit space is a place of stopover because of the influence of spatial area, visibility, historical area, iconic elements, social interaction, while the shelter space was not functionally visited due to the influence of minimizing visibility, social interaction, and arrangement of attribute elements.